Teaching strategies employed to develop language proficiency of grade 4 learners : the case of Toronto Primary School - Malatji, Molatelo Mary (My University, 2021)
The purpose of this study was to explore strategies employed by teachers to develop language proficiency of Grade 4 learners. Qualitative case study was adopted to identify and describe the effectiveness of strategies employed by teachers. Data collection was done using semi-structured interviews, non-participant observations and document analysis. Four (4) Grade 4 teachers who teach EFAL at Toronto Primary School participated in the study. The findings indicated that learner-centred strategies such as group work, peer teaching, scaffolding and discussion were effective in engaging learners in the learning and teaching process. Teachers also employed code switching and individual instruction as remedial strategies to further facilitate better understanding of the content. The findings also showed that sometimes the strategies were not effective due to disruptive behaviour. CAPS training, teaching experience and collaboration of teachers enabled teachers to execute the strategies successfully in regardless of scarcity of resources and overcrowded classrooms. The findings also revealed that teachers experienced challenges such as overcrowded classrooms, lack of resources, lack of teaching aids, time allocated to teach EFAL and lack of support from the parents to teach EFAL effectively and these challenges still need to be addressed to allow smooth learning and teaching of EFAL. Recommendations from the study were made on how teachers can overcome problems they experience in the teaching of EFAL. Key terms: EFAL, Learner-centred approach, Grade 4.
Thesis (M. A. (English Studies)) -- University of Limpopo, 2021
Keywords: EFL; Learner-centred approach; Grade 4 learners; English language - Study and teaching -- South Africa; English language -- Study and teaching (Primary); Activity programs in education; Code switching (Linguistics); English language -- Study and teaching (Primary) -- Foreign speakers